Strongly Positive Tissue Transglutaminase Antibody Assays without Celiac Disease - Hugh James Freeman (Canadian Journal of Gastroenterology)
Celiac disease is a small bowel disorder characterized by flattened villi and crypt hyperplasia, often with malabsorption. Improvement occurs with a gluten-free diet. Sensitive and specific assays (eg, immunoglobulin A antibodies to tissue transglutaminase [tTG]) that can be quantified appear to be valuable tools for population screening studies. In addition, their use is expanding widely in the clinical practice arena, being employed as a method of case finding. In this evaluation, clinical use of a commercially available test kit was explored. Of 1330 samples submitted to our hospital laboratory by physicians in British Columbia, Alberta and the Yukon Territory (from 1999 to 2003, inclusive), 96 patients (7%) had increased values (normal range greater than 20 units) and markedly increased levels greater than 100 units were detected in 36 patients (3%). Of these, 14 patients (almost 40%) were referred to gastroenterologists in our hospital and all 14 had small intestinal biopsies. Of these, three patients (more than 20%) did not have celiac disease. Two had normal small bowel biopsies and one had unclassified sprue or 'sprue-like' intestinal disease that failed to respond to a gluten-free diet. The other 11 had biopsy-defined celiac disease. While the tTG assay may be a useful predictor of celiac disease, small intestinal biopsy is still required to confirm the diagnosis. In clinical practice, even strongly positive tTG results are not specific in individual patients, do not necessarily correlate with the degree of severity of biopsy change and, as a result, are also unlikely to be useful for monitoring diet compliance.